2020
DOI: 10.1155/2020/2509454
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of M1/M2 Macrophages and Related Cytokines in Patients with Spinal Tuberculosis

Abstract: Background. Macrophages are important immune cells involved in Mycobacterium tuberculosis (M.tb) infection. To further investigate the degree of disease development in patients with spinal tuberculosis (TB), we conducted research on macrophage polarization. Methods. Thirty-six patients with spinal TB and twenty-five healthy controls were enrolled in this study. The specific morphology of tuberculous granuloma in spinal tissue was observed by hematoxylin-eosin (H&E) staining. The presence and distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…NUSAP1 regulates mitosis and chromosome segregation [ 40 ]. CD163 is a scavenger receptor specific to monocytes and macrophages and was associated with the polarization of macrophages into the M2 subtype [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…NUSAP1 regulates mitosis and chromosome segregation [ 40 ]. CD163 is a scavenger receptor specific to monocytes and macrophages and was associated with the polarization of macrophages into the M2 subtype [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that macrophage polarization was involved in the occurrence and development of TB [ 35 ]. Wang et al reported that two types of macrophage polarization (M1 and M2) were present in the tissues and peripheral blood of patients with STB, indicating that macrophages play proinflammatory and anti-inflammatory roles [ 36 ]. The results of the study indicated that M1 macrophages functioned at the crux of host defense by eliciting essential proinflammatory responses and bridging innate and adaptive immunities.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as aforementioned, M1 macrophages mediate inflammatory responses by producing copious amounts of proinflammatory cytokines such as TNF-α, IL-6, and IL-1β [ 82 ]. Among these, TNF-α participates in the mechanism of RSA by regulating stathmin-1 (STMN1) expression [ 83 ].…”
Section: Macrophagesmentioning
confidence: 99%